2005
DOI: 10.1093/rpd/nci325
|View full text |Cite
|
Sign up to set email alerts
|

Natural radioactivity in tap waters of Eastern Black Sea region of Turkey

Abstract: In this study, the activity concentrations of some radionuclides in tap water samples of the Eastern Black Sea region of Turkey were measured. The activity concentrations of radionuclides (214)Pb, (214)Bi, (40)K, (226)Ra and (137)Cs were determined using high resolution gamma ray spectrometry. Furthermore, (222)Rn activity concentrations in tap water samples were measured using Liquid Scintillation Counting. The mean specific activities of (214)Pb, (214)Bi, (226)Ra, (40)K, (137)Cs and (222)Rn in tap water samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…Results have been summarized by J. Longtin [4]. Mostly uranium isotopes, Subsequently extensive studies have been performed both on ground waters feeding public water resources [19][20][21][22], and on spring or bottled mineral waters [23][24][25][26][27][28][29][30][31]. Many other studies are available, including reports by national authorities [32][33][34].…”
Section: Available Results Of Monitoring Campaignsmentioning
confidence: 99%
“…Results have been summarized by J. Longtin [4]. Mostly uranium isotopes, Subsequently extensive studies have been performed both on ground waters feeding public water resources [19][20][21][22], and on spring or bottled mineral waters [23][24][25][26][27][28][29][30][31]. Many other studies are available, including reports by national authorities [32][33][34].…”
Section: Available Results Of Monitoring Campaignsmentioning
confidence: 99%
“…The area is generally gently sloping from southwest to east. The drainage density varies from 0.72 to 1.70 km/ km 2 and general ground elevation ranges from about 500 m amsl to 800 m amsl (Cevik et al 2006). The groundwater usually occurs at depth in the fractures and fault zone of the crystalline rocks under semi-confined to confined conditions.…”
Section: Geology and Hydrogeologymentioning
confidence: 99%
“…A comparative study of the activity concentrations of 226 Ra,232 Th and 40 K in water samples of the study area with the previous measurements from different countries of the world shows the average activities of 226 Ra are higher than those observed in Egypt (0.58 Bq.L -1 ) (Mourad et al, 2009), the Chittagong Region of Bangladesh (drinking water: 0.043 ± 0.017 Bq.L -1 ) , the Eastern Black Sea region of Turkey (tap water: 0.019 Bq.L -1 ) (Cevik et al, 2006), Qena, Egypt (drinking water: 0.048 ± 0.0259 Bq.L -1 , groundwater: 0.07918 ± 0.02886 Bq.L -1 ), Safaga-Quseir, Egypt (drinking water: 0.05624 ± 0.02849 Bq.L -1 , groundwater: 0.11285 ± 0.0333 Bq.L -1 ) (Khalifa, 2004), Tunisia (springs: 0.03404 -3.8961 Bq.L -1 ) (Labidi et al, 2002) and Hungary (bottled mineral water: 0.0999 to 2.997 Bq.L -1 ) (Somlai et al, 2002), while they are lower than those found in the Portuguese rivers Tejo and Duro (16.2 ± 6.7 and 19.8 ± 8.7 Bq.L -1 ), and the Bay of Bengal (surface seawater: 5.4 ± 2.4 to 29.0 ± 8.3 Bq.L -1 ) (Ghose et al, 2000). A very high concentration of 226 Ra was reported in the Ikaria Sea (1200 ± 1000 Bq.L -1 ), French rivers (1 to 730 Bq.L -1 ) and Czechoslovakia (10 to 3800 Bq.L -1 ) (Ghose et al, 2000).…”
Section: Soil and Water Samplesmentioning
confidence: 99%
“…The measured activity concentrations of 232 Th (3.82 ± 0.24 Bq.L -1 ) in the same water samples are higher than the previous results from Egypt (0.05 Bq.L -1 ) (Mourad et al, 2009), the Chittagong Region of Bangladesh (drinking water: 0.19 ± 0.05 Bq.L -1 ) , Qena, Egypt and Safaga-Quseir, Egypt (drinking water: 0.02923 ± 0.01665 Bq.L -1 , groundwater: 0.05143 ± 0.0222 Bq.L -1 ) (Khalifa, 2004). The concentration observed for 40 K is higher than that of the reported value from Egypt (0.05 Bq.L -1 ) (Mourad et al, 2009), the Eastern Black Sea region of Turkey (tap water: 0.019 Bq.L -1 ) (Cevik et al, 2006) and the Chittagong Region of Bangladesh (drinking water: 4.16 ± 1.58 Bq.L -1 ) .…”
Section: Soil and Water Samplesmentioning
confidence: 99%
See 1 more Smart Citation